SYNERGISTIC ANTIBIOIFLM ACTIVITY OF PROBIOTIC LACTOBACILLUS ACIDOPHILUS AND PUNICA GRANATUM L., AGAINST PSEUDOMONAS AERUGINOSA BIOFILM - Khursheed, Hadia; Qasim, Rimsha (Journal of Ayub Medical College Abbottabad, 2024)
Background: Antibiotic resistance is one of the most urgent public health concerns. Biofilm formation is well linked with chronic wounds, chronic obstructive pulmonary disease, urinary tract infections, and cystic fibrosis. Our goal was to assess the biofilm activity of P. aeruginosa and the individual and combined anti-biofilm forming activity of probiotic Lactobacillus acidophilus and Pomegranate peel extract Punica granatum L., against P. aeruginosa. Methods: A total of 150 swabs of urine, blood, pus, and CSF were collected from PNS Shifa Hospital Karachi, and P. aeruginosa was isolated and identified according to standard bacteriological methods. The ability of P. aeruginosa to form biofilms was assessed using a microtiter plate assay. Results: The anti-biofilm forming activity of pomegranate peels extract against P. aeruginosa was 29.26±19.09 whereas the anti-biofilm forming activity of Lactobacillus acidophilus against P. aeruginosa was 0.5Ã—106. When used in combination, there was significant synergistic activity between Punica granatum L. (pomegranate peel extract) and Lactobacillus acidophilus. Conclusion: The unique synergistic mixture of natural product extracts and probiotics has demonstrated more efficiency against rapidly evolving pathogens, serving as promising candidates for developing biofilm inhibitors and perhaps proving as possible environmentally friendly agents against bacteria that produce antibiotic-resistant biofilms.